The Molecular and Functional Interaction Between Membrane-Bound Organelles and Membrane-Less Condensates - Zhou, Chuankai (Frontiers in Cell and Developmental Biology, 2022)
A major recent advance in cell biology is the mechanistic and kinetic understanding of biogenesis of many membrane-less condensates. As membrane-less condensates and membrane-bound organelles are two major approaches used by eukaryotic cells to organize cellular contents, it is not surprising that these membrane-less condensates interact with the membrane-bound organelles and are dynamically regulated by cellular signaling, metabolic states, and proteostasis network. In this review, I will discuss recent progress in the biogenesis of membrane-less condensates and their connection with well-studied membrane-bound organelles. Future work will reveal the molecular and functional connectome among different condensates and membrane-bound organelles.